Stunting sebagai Fenomena Sosial Budaya: Tinjauan terhadap Mitos dan Praktik Tradisional Etnis Melayu Sambas di Desa Sebayan - Musa, Pabali (Universitas Tanjungpura, 2025)
Stunting remains a serious public health issue in Indonesia, including in the border area of Sambas District, West Kalimantan. Sebayan Village records one of the highest stunting prevalence rates, reaching 36.61%. This study aims to identify socio-cultural factors contributing to stunting, with a focus on parenting patterns, economic conditions, local myths, and traditional feeding practices for infants and toddlers. The research employs a descriptive qualitative method through in-depth interviews with key informants, including village officials, local health workers, sub-district authorities, and representatives from the community health centre (Puskesmas). The analysis takes into account the social, cultural, and economic contexts of the local community. The findings reveal four primary factors contributing to stunting in Sebayan Village. First, suboptimal parenting practices, where children are often left in the care of grandparents, result in the lack of exclusive breastfeeding. Second, local myths such as prohibitions against children eating water spinach and the consumption of black pepper herbal drinks after childbirth negatively affect child nutrition. Third, traditional feeding practices, such as giving bubur koleh (a local porridge), often increase health risks due to their unhygienic nature. Fourth, economic limitations restrict families’ ability to provide balanced nutrition.